Loop ileostomy closure: a retrospective comparison of three techniques. Issue 9 (17th May 2020) - Lord, Ian; Reeves, Lesley; Gray, Andrew; Woodfield, John; Clifford, Kari; Thompson‐Fawcett, Mark
Abstract: Background: Loop ileostomy (LI) formation is a common practice for patients undergoing low anterior resection or restorative ileo‐anal pouch surgery. Ileostomy closure can be performed using a stapled or hand‐sewn technique, with or without resection. If hand‐sewn, the closure can be one or two layers. Randomized controlled trials have not demonstrated one technique to be superior, and meta‐analyses are limited by the heterogeneity of published studies. Our primary aim is to compare stapled ileostomy closure with single‐ and two‐layer hand‐sewn closures. Methods: This retrospective, single‐centre cohort study included patients undergoing LI closure between January 1999 and April 2016. Patient demographics, anastomotic technique, operative time and patient outcomes were collected. Results: Our analysis included 244 patients (median age 67 years, 43.4% female). There were no significant differences in mean operative times (71.5, 73.1 and 88.5 min, for stapled, single‐ and two‐layer hand‐sewn closures, respectively, adjusted overall P = 0.262), or morbidity (21.5% versus 20.4% versus 17.6%, adjusted overall P = 0.934) between stapled or hand‐sewn anastomoses, and no mortality. Once adjusting for age, sex, American College of Anaesthesiology grade, and consultant surgeon, the length of stay was different (overall P = 0.034), being similar between stapled and single‐layer closures (4.2 versus 5.5 days, P = 0.105), but significantly different between stapled and two‐layer closures (4.2 versus 8.3 days, P = 0.026). Conclusion: Stapled and single‐layered hand‐sewn closures are similar in length of procedure, length of stay and complication rates. A two‐layer, hand‐sewn technique is associated with a significant increase in stay compared to a stapled ileostomy closure. Abstract : Loop ileostomy formation is a common practice for patients undergoing low anterior resection or restorative ileo‐anal pouch surgery. Stapled and single‐layered hand‐sewn closures are similar in length of procedure, length of stay and complication rates. A two‐layer, hand‐sewn technique is associated with a significant increase in stay compared to a stapled ileostomy closure.